2008
DOI: 10.1093/toxsci/kfn025
|View full text |Cite
|
Sign up to set email alerts
|

Toxicogenomic Dissection of the Perfluorooctanoic Acid Transcript Profile in Mouse Liver: Evidence for the Involvement of Nuclear Receptors PPARα and CAR

Abstract: A number of perfluorinated alkyl acids including perfluorooctanoic acid (PFOA) elicit effects similar to peroxisome proliferator chemicals (PPC) in mouse and rat liver. There is strong evidence that PPC cause many of their effects linked to liver cancer through the nuclear receptor peroxisome proliferator-activated receptor alpha (PPAR alpha). To determine the role of PPAR alpha in mediating PFOA transcriptional events, we compared the transcript profiles of the livers of wild-type or PPAR alpha-null mice expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
111
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 178 publications
(123 citation statements)
references
References 37 publications
9
111
0
Order By: Relevance
“…This adds DEHP to the growing list of environmental contaminants activating CAR [54,[75][76][77], further stressing the need to evaluate M a n u s c r i p t 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 (n = 10 for each group). Significant differences were analyzed by one-way ANOVA followed by Student's t test.…”
Section: Discussionmentioning
confidence: 99%
“…This adds DEHP to the growing list of environmental contaminants activating CAR [54,[75][76][77], further stressing the need to evaluate M a n u s c r i p t 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 (n = 10 for each group). Significant differences were analyzed by one-way ANOVA followed by Student's t test.…”
Section: Discussionmentioning
confidence: 99%
“…4C). This non-PPARα-mediated increase in Mdr2 mRNA may likely be attributable to the increase in bile acid at high doses 27) or other nuclear receptors 28) . To confirm adaptive phospholipid transport, we examined the biliary bile acid to phospholipid (BA/PL) ratio (Fig.…”
Section: Quantitative Rt-pcr For Mdr2 Bile Acids/phospholipids Ratiomentioning
confidence: 99%
“…External stimuli, such as drugs, poisons, etc. can cause hepatic changes in lipid metabolism, steroid metabolism, and homeostasis (Lockhart et al, 2003;Xu et al, 2005;Rosen et al, 2008). Liu et al found glycolysis and fat metabolism had significant changes in the process of tumorigenesis, providing the essential materials for the growth, hyperplasia, and metastasis of tumor cells (Liu et al, 2009).…”
Section: Discussionmentioning
confidence: 99%